YOSHLARNING FUQAROLIK TARBIYASIDA FUQAROLIK POZITSIYANING OʻRNI - Orınbetov, N.T. (SCIENCE and SOCIETY, 2024)
This article talks about the citizenship education of young people in our country, the role of the citizenship position in it, its problems, and foreign experiences.
Keywords: globalization; civic upbringing; civic education; civic stand; values; legal education; legal nurturing; legal culture